1994
DOI: 10.1002/ijc.2910570614
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxicity of the anticancer agents cisplatin and taxol during cell proliferation and the cell cycle

Abstract: The overt effects of the anti-cancer drugs cisplatin (cis-DDP) and taxol appear to be DNA modification and microtubule stabilization respectively, yet the mechanisms by which these drugs elicit tumor cell death are not well understood. In this report cell sensitivities to cis-DDP and taxol were accurately determined as a function of cell proliferation and cell cycle stage. Quiescent fibroblasts restimulated to synchronously enter the cell cycle become maximally sensitive to cis-DDP immediately preceding DNA sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
108
0

Year Published

1997
1997
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 175 publications
(115 citation statements)
references
References 27 publications
(10 reference statements)
7
108
0
Order By: Relevance
“…We found here that the delay in mitotic exit was associated with apoptosis in the NIH-OVCAR-3 cell line. Several studies have indicated that p34 cdc2 activity mediates apoptotic cell death (Shi et al, 1994;Shimizu et al, 1995), and it has been suggested that p34 cdc2 plays a role in paclitaxel induced-apoptosis (Donaldson et al, 1994). In the present study, we found that a prolonged activation of p34 cdc2 in the absence of p21 expression was associated with apoptosis, whereas apoptosis did not occur when p21 was elevated enabling an earlier inhibition of p34 cdc2 activity.…”
Section: In¯uence Of Antisense-p21 On Cell Survival After Paclitaxel supporting
confidence: 57%
“…We found here that the delay in mitotic exit was associated with apoptosis in the NIH-OVCAR-3 cell line. Several studies have indicated that p34 cdc2 activity mediates apoptotic cell death (Shi et al, 1994;Shimizu et al, 1995), and it has been suggested that p34 cdc2 plays a role in paclitaxel induced-apoptosis (Donaldson et al, 1994). In the present study, we found that a prolonged activation of p34 cdc2 in the absence of p21 expression was associated with apoptosis, whereas apoptosis did not occur when p21 was elevated enabling an earlier inhibition of p34 cdc2 activity.…”
Section: In¯uence Of Antisense-p21 On Cell Survival After Paclitaxel supporting
confidence: 57%
“…Previous research has shown the temporal association of paclitaxel-mediated apoptosis and p34cdc2 activation, and also has demonstrated the attenuation of paclitaxel-mediated apoptosis by inhibition of p34cdc2 activity (Donaldson et al, 1994;Shen et al, 1998;Yu et al, 1998). These studies concluded that the activity of p34cdc2 was required for paclitaxelmediated apoptosis (Yu et al, 1998).…”
Section: Discussionmentioning
confidence: 98%
“…In the induced RKO cells, the cell cycle was arrested wholly in G1 phase by p27 Kip1 and in G1 and G2/M by p21 Waf1 (Figure 2b), whereas the increased p34cdc2 activity and cell cycle arrest associated with paclitaxel treatment is known to occur in G2/M phase (Donaldson et al, 1994). We therefore sought to determine in which phase RKO cells accumulated when they were treated with paclitaxel and were subsequently induced to express p21 Waf1 or p27 Kip1 .…”
Section: Dissociation Of Paclitaxel-mediated Cytotoxicity and Elevatementioning
confidence: 99%
“…Sena and Chen (1998) used the micronucleated cell assay and Swiss albino mice to evaluated the in vivo bone marrow cell mutagenic potential of 25, 50 and 80% of the LD 50 dose of orally administered Copaifera langsdorfii oleoresin and demonstrated a statistically significant increase micronucleated cells (and hence mutagenic action) 836 Maistro et al only at high doses, although these authors used a higher maximum dose than we did. Donaldson et al (1994) extensively investigated the cytotoxicity of the antimitotic antitumor diterpene taxol derived from the yew tree Taxus brevifolia and showed that the antimitotic effect of taxol classified it as an important anticancer agent. A genotoxicity study by Dias et al (1997) showed that taxol had no radio-sensitizing effect on chromosomal aberrations induced by gamma radiation and also did not increase doxorubicin-induced chromosomal aberrations in in vitro Chinese hamster ovary cells.…”
Section: Indicates That C Duckeimentioning
confidence: 99%